Web Technologies and Applications APWeb 2014 Workshops, SNA, NIS, and IoTS, Changsha, China, September 5, 2014, Proceedings - Han, Weihong; Huang, Zi; Hu, Changjun; Zhang, Hongli; Guo, Li (Information Systems and Applications, incl. Internet/Web, and HCI, 2014)
This book constitutes the refereed proceedings of the workshops held at the 16th Asia-Pacific Web Conference, APWeb 2014, in Changsha, China, in September 2014. The 34 full papers were carefully reviewed and selected from 59 submissions. This volume presents the papers that have been accepted for the following workshops: First International Workshop on Social Network Analysis, SNA 2014; First International Workshop on Network and Information Security, NIS 2014; First International Workshop on Internet of Things Search, IoTS 2014. The papers cover various issues in social network analysis, security and information retrieval against the heterogeneous big data.